Understanding Children's Cognitive Development: Piaget's and Vygotsky's Views, and Relevance in the Qur'an's Perspective - Mukhmad Averros Azzam Al Islami; Sedya Santosa (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Cognitive development is very important for everyone to understand, both teachers and parents. The theory of cognitive development emerged in the middle of the century, known as the theory of Piaget and Vygotsky. However, long before these two theories existed, Islam had already explained children's cognitive development in the Al-Qur'an. The purpose of this article is to understand the development of theory according to Jean Piaget and Vygotsky and its relevance from the perspective of the Al-Qur'an. The research method uses literature studies which involve searching for data from various reference sources such as research journals, literature reviews, and materials related to children's cognitive development. The results of this research show that the views of Piaget and Vygotsky and the views of the Koran are not much different, if combined they will provide a more comprehensive picture of children's cognitive development. Piaget showed that children develop through interactions with the physical world, while Vygotsky emphasized the importance of social interactions. The Koran supports both of these views by highlighting the importance of using the senses and heart to learn as well as the importance of guidance from those who are more knowledgeable.